Muscle Evaluation in Axial Spondyloarthritis—The Evidence for Sarcopenia - Valido, Ana; Crespo, Carolina Lage; Pimentel-Santos, Fernando M. (Frontiers in Medicine, 2019)
Sarcopenia is a syndrome defined as a progressive and generalized skeletal muscle disorder associated with increased likelihood of adverse outcomes as falls, fractures, physical disability and death. The actual definition of sarcopenia is based in reduction of measures for three parameters- strength, muscle mass quantity or quality and physical performance (the determinat of severity). Muscle wasting is a common feature in several chronic diseases, such as spondyloarthritis (SpA), that significantly increases patient’s morbidity and mortality. Although, the huge progress in this field over the last years, the absence of a clear definition and clear diagnostic criteria of sarcopenia, justify the inconsistent information regarding muscle involvement in SpA. Thus, the aim of this review is to collect relevant evidence of muscle changes occurring during the disease process in published literature, according to recommended tools for sarcopenia evaluation proposed by the European Working Group on Sarcopenia in Older People 2 (EWGSOP2). In addition, data on histological, electromyography and biochemical muscle analyses in SpA patients are also reviewed. Overall, a reduction on muscle strength with a systemic decrease in lean mass seems to be associated with a gait speed compromise. This information is usually fragmented with no studies considering the three parameters all together. This paper represents a call-to-action for new studies design in future research.